(untitled) (Global Journal of Management and Business Research, 2014)
Segmentation is the need of modern marketing because to serve the entire market is no more profitable. The very first step of market segmentation is to identify which variables are most important to segment or to group the customers into homogeneous groups. Usually more than one variable is used to give the description of market segments. The most common variables used are demographic, geographic, psychographic, and behaviuoral. In the present study demographic and psychographic variables are taken into consideration. The human behavior is dominated by the internal psycho of the individual and the way they treat with the society. The main psychographic variables as values, social interest, attitude and lifestyle are broadly taken into consideration. Cluster analysis is used to segment the market. Factor analysis is used to identify the factors for segmentation.